On the Trajectory Planning for Energy Efficiency in Industrial Robotic Systems † - Giovanni Carabin; Lorenzo Scalera (Robotics, 2020)
In this paper, we present an approach for the minimum-energy trajectory planning in industrial robotic systems. The method is based on the dynamic and electro-mechanical modeling of one-degree-of-freedom systems and the derivation of the energy formulation for standard point-to-point trajectories, as, for instance, trapezoidal and cycloidal speed profiles. The proposed approach is experimentally validated on two robotic systems, namely a linear axis of a Cartesian manipulator built in the 1990’s, and a test bench composed of two servomotors directly connected or coupled by means of a planetary gear. During the tests, the electrical power expended by the systems is measured and integrated over time to compute the energy consumption for each trajectory. Despite the limitations of the energy measurement systems, the results reveal a trend in agreement with the theoretical calculations, showing the possibility of applying the method for enhancing the performance of industrial robotic systems in terms of energy consumption in point-to-point motions.